Wrocław Śródmieście – specific features and development prospects - Zakrzewska-Półtorak, Alicja (Wrocław Śródmieście – specyfika i perspektywy rozwoju, 2016)
The aim of this paper is to determine the specificity and importance of Wrocław-Śródmieście (the important part of Wrocław, the former district) in the economy of Wrocław and its prospects for development, taking into account strengths and weaknesses. The object of this research is the statistical unit of Wrocław defined by the boundaries of the former district − Wrocław-Śródmieście. The research covers the period (as the availability of statistical data) for the years 2009-2015. The author used a descriptive method, simple statistical methods, an analysis of literature and source documents, a deductive method and an empirical inference
Biblioteka Regionalisty, 2016, Nr 16, s. 133-141
Keywords: Wrocław-Śródmieście; local development; economic activity; rozwój lokalny; aktywność gospodarcza